Assessing the Efficiency of Village Fund Expenditures in Infrastructure Projects: A Public Sector Financial Accounting Approach - Loly, Loly; Septa Diana Nabella; Erina Alimin; Affendy Abu Hassim; Cici Handayani (Journal of Finance Integration and Business Independence, 2025)
This study investigates the efficiency of Village Fund expenditures in infrastructure projects within Kutambaru Subdistrict, Langkat Regency, and identifies which villages demonstrate efficient or inefficient budget utilization. The analysis is based on secondary data, including Village Budget (APBDes), Budget Plans (RAB), budget realization reports, and accountability reports from eight villages. Efficiency is measured using four public sector accounting indicators: budget-realization ratio, cost-to-physical-output ratio, cost variance (CV), and value for money (VfM). Findings reveal varying levels of efficiency across villages. Kaperas, Namotogan, and Rampal are categorized as the most efficient, characterized by low cost per meter, positive cost variance, and high VfM scores. In contrast, Kuta Gajah and Sulkam are deemed inefficient due to cost overruns (negative CV), high cost per meter, and low infrastructure utility. These inefficiencies are primarily attributed to weaknesses in budget planning (RAB), inaccurate volume estimations, uneconomical material procurement, and suboptimal technical supervision. The study highlights the importance of comprehensive financial performance evaluation at the village level using a value for money approach to ensure that Village Funds yield economic, efficient, and effective development outcomes. The findings are expected to serve as a reference for village and regional governments in improving infrastructure budget governance.